ANALISIS PROFIL WILAYAH DALAM PERENCANAAN AGROWISATA BERBASIS KOMODITI PERKEBUNAN (STUDI KASUS DI KABUPATEN JEMBRANA) - Satriawan, I Ketut (Agrotekno; Vol. 14, No. 1 Februari 2008, 2012)
This research objective was to know the profile of an area which will be developed as an agro-tourism area in order to increase the economic activities of the area. The profile of the area was studied through a potency analysis by using a factor analysis on several economic potential namely agro-estate, industry, and tourism. Meanwhile, the projection analysis od estate commodity production and tourism arrival when using a forecasting method. Jembrana Regency has some centers of estate commodity which could developed as an agro-tourism area. This potency is also supported by the existence of industrial sector and the increasing trend of tourism arrival. So that, development of new tourist objects, such as agro-tourism at Jembrana Regency is still prospective.
Keywords: profile of an area, agro tourism, tourism